- 82
- 0
I am having to do a proof on a problem and am not really seeing it for some reason. Maybe it's because I have been doing the homework for so long.
Prove that if A is nonsingular then A^T is nonsingular and
(A^T)^-1 = (A^-1)^T
Hint: (AB)^T = B^T*A^T
I understand the hint, but I cant seem to get an image of the actual problem.
Can anyone help me?
Prove that if A is nonsingular then A^T is nonsingular and
(A^T)^-1 = (A^-1)^T
Hint: (AB)^T = B^T*A^T
I understand the hint, but I cant seem to get an image of the actual problem.
Can anyone help me?